Synthesis of N-oxyethylene substituted imidazolium-based zwitterions as a recyclable solvent for cellulose dissolution - Jadhav, Sachin; Ganvir, Vivek; Singh, Madan Kumar; Shanmuganathan, Kadhiravan (Cellulose, 2023)
Cellulose is a readily available, renewable, and natural biomaterial that has the potential to replace synthetic fibres. However, their processing to shaped materials such as fibre or film is still complex and restricted due to its insolubility in most conventional solvents. Herein, we present the synthesis and cellulose dissolution characteristics of a new class of recyclable zwitterions composed of tethered N-oxyethylene substituted imidazolium cation and alkyl carboxylate anion. Investigations on cellulose dissolution showed that increasing the alkyl chain length of carboxylate anion and introduction of oxyethylene unit on imidazolium ring led to better cellulose dissolution ability, and up to 12% (w/w) cellulose could be dissolved in aqueous zwitterions at 105 degrees C. The thermal behavior of zwitterions and their cellulose solutions was characterized by TGA and found to be more stable than the NMMO and Lyocell solutions. Rheological characterization of cellulose solutions revealed viscoelastic behavior and zero shear viscosity of 6-12% (w/w) cellulose solution in hexanoate containing aqueous zwitterion was 555 to 5900 Pa.s at 120 degrees C. The characteristics of cellulose solution indicate its potential for processing to cellulose fibre by extrusion through a tiny spinneret. Physico-chemical analysis of regenerated cellulose indicates that zwitterions cause no adverse effect on cellulose structure and morphology during dissolution. The zwitterions are recovered after the cellulose regeneration process, and the recovery was found to be 99.6% after purification using the ion-exchange method.
Keywords: Carboxylate anion; Cellulose dissolution; Oxyethylene unit; Regenerated cellulose; Rheology; zwitterions

Structure and properties of the cellulose fibres spun from imidazolium-based carboxylate functionalized zwitterionic liquid - Jadhav, Sachin; Singh, Dhirendra; Gupta, Deepika; Ganvir, Vivek; Singh, Madan Kumar; Shanmuganathan, Kadhiravan (CARBOHYDRATE POLYMERS, 2025)
Keywords: cellulose; Direct dissolution; Zwitterionic liquid